Ribosomal Protein L40e Fused With a Ubiquitin Moiety Is Essential for the Vegetative Growth, Morphological Homeostasis, Cell Cycle Progression, and Pathogenicity of Cryptococcus neoformans - Zhao, Jingyu; Yang, Yali; Fan, Yibin; Yi, Jiu; Zhang, Chao; Gu, Zhongkai; Pan, Weihua; Gu, Julin; Liao, Wanqing; Fang, Wei (Frontiers in Microbiology, 2020)
Ubiquitin is a highly conserved protein required for various fundamental cellular processes in eukaryotes. Herein, we first report the contribution of the ubiquitin fusion protein Ubi1 (a ubiquitin monomer fused with the ribosome protein L40e, Rpl40e) in the growth and pathogenicity of Cryptococcus neoformans. UBI1 deletion resulted in severe growth restriction of C. neoformans, whose growth rate was positively correlated with UBI1 expression level. The growth defect of the ubi1∆ strain could be closely associated with its morphological abnormalities, such as its reduced ribosome particles. In addition, the ubi1∆ mutant also displayed increased cell ploidy, cell cycle arrest, and decreased intracellular survival inside macrophages. All these phenotypes were reversed by the reconstitution of the full-length UBI1 gene or RPL40a domain. Mouse survival and fungal burden assays further revealed a severely attenuated pathogenicity for the ubi1∆ mutant, which is probably associated with its reduced stress tolerance and the induction of T-helper 1-type immune response. Taken together, Ubi1 is required for maintaining the vegetative growth, morphological homeostasis, cell cycle progression, and pathogenicity in vivo of C. neoformans. The pleiotropic roles of Ubi1 are dependent on the presence of Rpl40e and associated with its regulation of cryptococcal ribosome biogenesis.